Micro-Strategies of Post-Method Language Teaching Developed for Iraqi EFL Context - Assist. Lect. Ghaith Saleh Mahdi; Assist. Lect. Mohammed Salim Al-Hassani; Assist. Lect. Duaa Hamid Ali Alwani (Zien Journals, 2022)
Micro-strategies for macro-strategies are the focus of this essay, which follows the approach structure. One or two micro-strategies accompanied the ten macro-strategies in the framework. In Iraq, several of those micro-strategies are not applicable. The researchers used a random sample of 24 language teachers for the study. For starters, macro and micro-strategies were taught together in the classroom. On the other hand, the micro-strategies did not fit the Iraqi environment for English language learning. Participants have been asked to think and develop micro-strategies for each macro-strategies by the researchers. Afterward, the participants' micro strategies were cut and tweaked to make them more workable.
Keywords: strategies; focus; essay; accompanied